The Role of Green Marketing Dimensions in Purchase Decisions and Brand Loyalty Among Millennial and Gen Z Consumers: A Study of Erigo - Abhiyoga Deyandra Putra; Muchsin Saggaff Shihab (Journal Research of Social Science, Economics, and Management, 2026)
Sustainability issues are increasingly becoming a top agenda in global business, encouraging companies to integrate green marketing, which emphasizes environmentally friendly aspects in products, pricing, distribution, and promotion—especially to meet the preferences of younger generations who are increasingly concerned about ethical values and environmental responsibility in purchasing decisions. This research aims to analyze the influence of green marketing on purchase decisions and brand loyalty among Millennial and Generation Z consumers of the local fashion brand Erigo. This research employed a quantitative approach using a survey method. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results show that all dimensions of green marketing, including green product, green distribution, green price, and green promotion, have a significant effect on purchase decisions. Meanwhile, for brand loyalty, only green product, green distribution, and green price have a significant effect, while green promotion does not. These findings indicate that green marketing strategies play an important role in influencing consumers’ purchase decisions; however, brand loyalty is more strongly influenced by consumers’ direct experiences with the product, distribution, and price perception.